Analysis of cobalt, tantalum, titanium, vanadium and chromium in tungsten carbide by inductively coupled plasma - optical emission spectrometry. - Rohwer, Egmont Richard (University of Pretoria, 2013)
Dissertation (MSc (Chemistry))--University of Pretoria, 2007.